Principals’ Perceptions of Transformational Leadership in Secondary School of Muzaffarabad Azad Kashmir - Mughal, Inaamul Haq; Atta, Batool; Khan, Adeel Ahmed; Zareen, Syed Jawad (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the Levels of transformational leadership among secondary school principals in Muzaffarabad, by a focus on its essential role in shaping educational environments. Transformational leadership, characterized by its emphasis on inspiring and motivating followers, encouragement innovation, and driving progressive change, holds significant importance in the realm of educational institutions. The research employs a quantitative methodology, involving 90 secondary school principals, to investigate into the comprehension and implementation of transformational leadership. Descriptive statistics indication a moderate level of transformational leadership displayed by principals across various dimensions. The findings add valuable understandings to the continuing discourse on educational leadership, involvement associations for the development of impactful platforms and knowledgeable policies. This research highlights the requirement for nuanced leadership approaches to promote educational consequences in Muzaffarabad, underscoring the transformative prospective of effective leadership in the energetic landscape of secondary education.